Foundations of the knowledge economy : innovation, learning and clusters - Westeren, Knut Ingar, 1950- (Edward Elgar, 2012)
"This book presents new evidence concerning the influential role of context and institutions on the relations between knowledge, innovation, clusters and learning. From a truly international perspective, the expert contributors capture the most interesting and relevant aspects of knowledge economy. They explore an evolutionary explanation of how culture can play a significant role in learning and the development of skills. Presenting new data and theory developments, this insightful book reveals how changes in the dynamics of knowledge influence the circumstances under which innovation occurs."--Resumé vydavatele
Keywords: znalostní ekonomika; znalostní management; učící se organizace; inovace; klastry (ekonomie); knowledge economy; knowledge management; organizational learning; innovations; clusters (economics); kolektivní monografie; elektronické knihy; collective monographs; electronic books